Railtown : the fight for the Los Angeles metro rail and the future of the city - Elkind, Ethan N., 1976- (University of California Press, 2014)
The familiar image of Los Angeles as a metropolis built for the automobile is crumbling. Traffic, air pollution, and sprawl motivated citizens to support urban rail as an alternative to driving, and the city has started to reinvent itself by developing compact neighborhoods adjacent to transit. As a result of pressure from local leaders, particularly with the election of Tom Bradley as mayor in 1973, the Los Angeles Metro Rail gradually took shape in the consummate car city. Railtown presents the history of this system by drawing on archival documents, contemporary news accounts, and interviews with many of the key players to provide critical behind-the-scenes accounts of the people and forces that shaped the system.